Understanding Buyer Sypplier Relationship in The Kids Wear Industry in India-Examining The Role of Various Constructs - Kasat, Arpit (2008)
This study investigates the buyer supplier relationships and the role of various constructs in the kids wear market in India. It focuses on the budding unorganized segment of the kids wear industry. The purpose of the study is to analyze the changes within the industry and its effects on the unorganized segment. It primarily concentrates on the growing importance of the buyer supplier relationship in this sector and factors contributing to strengthen it. This paper aims to contribute to the existing literature on buyer supplier relationship by pondering on this untouched segment. Concentrating on the kids wear industry the dissertation focuses on how to establish and maintain long term relationships with the big retail stores. The retail giants, who focus on reducing costs and enhancing supplier-buyer-customer relationships, make it a challenging job for the manufacturers to reach their specifications. Hence my research concentrates on the importance of setting up relationship with the big buyers, the problems faced in doing so and features which enhance the relationship as well. The aim of this paper is to attempt to understand how relationship building helps both the suppliers and buyers along with analysing the importance of each construct in the relationship from a supplier perspective. In order to reach our purpose semi structured interviews were used, which comprised of interviews with suppliers and surveys focusing on suppliers as well as buyers.